Research on the math models of the combustion oil consumption of the farm transport machineries - CHEN Li-neng; LING Hong; XU Zhan-feng; WANG Fei (浙江大学学报. 农业与生命科学版, 2003)
The combustion oil consumption for a farm transport machinery is a main one of consumption items. By means of drawing a equivalent model from process of the farm transportation, two models were put forward. Further, the math models of the combustion oil consumption of the farm transport machineries were established. The factors of structure and utilization futures for transport machineries were constructed in these ones. It also proved that the models were reasonable by practical tests on road.